A Simple Task Uncovers a Postdictive Illusion of Choice. (June 2016) - Bear, Adam; Bloom, Paul
Do people know when, or whether, they have made a conscious choice? Here, we explore the possibility that choices can seem to occur before they are actually made. In two studies, participants were asked to quickly choose from a set of options before a randomly selected option was made salient. Even when they believed that they had made their decision prior to this event, participants were significantly more likely than chance to report choosing the salient option when this option was made salient soon after the perceived time of choice. Thus, without participants' awareness, a seemingly later event influenced choices that were experienced as occurring at an earlier time. These findings suggest that, like certain low-level perceptual experiences, the experience of choice is susceptible to "postdictive" influence and that people may systematically overestimate the role that consciousness plays in their chosen behavior.